Tanggungjawab PT. Asuransi Jiwasraya (Persero) Atas Perbuatan Wanprestasi Terhadap Tertanggung - Vina Ramadhina Malawat; Merry Tjoanda; Novyta Uktelseja (Faculty of Law, Universitas Pattimura, 2023)
Introduction: An agreement is an agreement made by two or more people who bind themselves to carry out a thing, which if one party does not fulfill or violates the agreement made then that party has defaulted.Purposes of the Research: The main problem in this thesis is the form of default committed by PT Asuransi Jiwasraya (Persero) against the insured and the responsibility of PT Asuransi Jiwasraya (Persero) for the losses experienced by the insured. This study aims to find out and understand the form of default committed by PT Asuransi Jiwasraya (persero) and the responsibility of PT Asuransi Jiwasraya for the losses experienced by the insured.Methods of the Research: This research uses normative juridical research using a case approach, statutory approach and conceptual approach.Results of the Research: The results of the research conducted, PT Asuransi Jiwasraya did not fulfill its obligations as an insurer or its successor according to the law that received the transfer of rights and obligations related to policy management, either partially or completely, from PT Asuransi Jiwasraya (Persero), while the insured fulfilled his obligations in the agreement agreed by both parties. sides